INFLUENCIA DE LAS FASES LUNARES DENTRO DE ALGUNOS PROCESOS REPRODUCTIVOS EN BOVINOS DE GRUPOS RACIALES DIVERSOS - AGUIRRE RIOFRIO, EDGAR LENIN (2010)
The results of the present investigation arose of the information collected from 828 registrations of natural heat, 302 data of births and 2 thesis on the influences of the lunar phases in the programmed reproduction of bovine, determined that the natural heat and the births in bovine.